Da'wah strategy of the Indonesian Ulema Council in broadcasting wasathiyah islamic values in Wonogiri - Syarifuddin, Muhammad; Riyadi, Agus; Ali, Mukti (Jurnal Ilmu Dakwah, 2024)
Purpose – This study aims to determine the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) Da'wah Strategy in Wonogiri in broadcasting Wasathiyah  Islamic values in Wonogiri as well as the supporting and inhibiting factors of the MUI Da'wah Strategy in Wonogiri.Method – This research is qualitative research, Data was collected by several data collection techniques: Observation, Interview, Documentation. The data analysis process is carried out throughout the research process, from planning and data collection to interpretation or interpretation of data or the content of data discussion in the field.Result  – This research shows that there are three da'wah strategies used by MUI Wonogiri, namely: (1) Sentimental Da'wah Strategy (Al-Manhaj 'athifi), (2) Rational Da'wah Strategy (Al-Manhaj Al-Aqli), (3) Sensory Da'wah Strategy (Al-Manhaj Al-Hissi).Implication – The implications of this research are related to the importance of the da'wah movement of the Indonesian Ulema Council Wonogiri in strengthening the value of Wasathiyah  IslamOriginality/Value – This study analyzes the views of the Da’i of the Wonogiri Indonesian Ulema Council on the understanding of wasathiyah Islam, and the activities of the da'wah movement in strengthening the understanding of Wasathiyah  Islamic Values.***Tujuan - Penelitian ini bertujuan untuk mengetahui Strategi Dakwah MUI di Wonogiri dalam menyiarkan nilai-nilai Islam Wasathiyah  di Wonogiri serta faktor-faktor pendukung dan penghambat Strategi Dakwah Majelis Ulama Indonesia (MUI) di WonogiriMetode - Penelitian ini merupakan penelitian kualitatif, Data dikumpulkan dengan beberapa teknik pengumpulan data: Pengamatan, Wawancara, Dokumentasi. Proses analisis data dilakukan selama proses penelitian, mulai dari perencanaan dan pengumpulan data hingga interpretasi atau interpretasi data atau isi pembahasan data di lapanganHasil  - Penelitian ini menunjukkan bahwa: ada tiga strategi dakwah yang digunakan oleh MUI Wonogiri, yaitu: (1) Strategi Dakwah Sentimental (Al-Manhaj 'athifi), (2) Strategi Dakwah Rasional (Al-Manhaj Al-Aqli), (3) Strategi Dakwah Sensorik (Al-Manhaj Al-Hissi).Implikasi– Implikasi dari penelitian ini terkait pentingnya gerakan dakwah Majelis Ulama Indonesia Wonogiri dalam memperkuat nilai Islam Wasathiyah Orisinalitas/Nilai - Penelitian ini menganalisis pandangan Da’i Majelis Ulama Indonesia Wonogiri terhadap pemahaman Islam Wasathiyah , dan aktivitas gerakan dakwah dalam memperkuat pemahaman Nilai-Nilai Islam Wasathiyah